Aplikasi Penjualan Griptape Dengan Menggunakan Infinitemonkeys(Studi Kasus Di Toko Lucker) - Faizal Arifianto, Deddy, Heru Supriyono, ST. MSc. PhD (2017)
Skateboard in Indonesia is now experiencing very rapid progress. Many of the young children to the elderly are now many are fond of this sport. But now there are many facilities in the form of applications to support this sport. Thus the authors wanted to make ecommerce system is to facilitate the application of sales griptape skateboard enthusiasts. The purpose of making this application is to facilitate buyers to choose griptape with images provided on the application, the method used in the making of this application is a method of System Development Life Cycle (SDLC), ranging from the search for data and information on griptape be sold by interviewing the users skateboard. Then the data that was obtained uploads using infinitemonkeys. As for e-comerce system in use is with infinitemonkeys is an application to make the application easier and opensource. So as to facilitate the skateboarder choose griptape desired. The results of this research include HTML5 system that contains the type griptape skateboard that will be sold by Shop Lucker and the like which way to order and buy the griptape